Islam, Women and Fertility in Sudan - Alnory, Ahmed Hamad (Gezira Journal of Economic and Social Sciences; مجلد 1 عدد 2 (2010), 2010)
The paper analyses the Western perception about women, Islam and Fertility. A perception that has been embodied in what is termed "the Islamic Hypothesis. The arguments for and against the hypothesis are critically presented. The assertions of the hypothesis are then tested using Sudan data from different sources, but it is to be noted that much of data used pertain to the time period where the Islamic hypothesis began to appear in the literature. The paper concludes that both arguments of the advocates of the Islamic hypothesis and their opponents are invalid for the case of Sudan.